Audiological findings in Brown Vialetto-Van-Laere Syndrome: A scoping review - Débora de Oliveira Rolim; Leticia Cristina Vicente; Hugo Amilton Santos de Carvalho; Rebeca Lorrane Santana Santos; Rivadávio Fernandes Batista de Amorim; Fayez Bahmad, Jr (Brazilian Journal of Otorhinolaryngology)
Objective: This study aimed to characterize audiological porfile in inviduals with Brown-Vialetto-Van Laere syndrome (BVVLS). Methods: This is a scoping review following the methodological structure developed by the Joana Briggs Institute (JBI). The PCC mnemonic was used to elaborate the research question, which resulted in the research question: “What are the audiological findings in individuals with BVVLS?”. Results: All of the studies included in this review were case reports. The main audiological findings are sensorineural hearing loss and Auditory Neuropathy Spectrum Disorder (ANSD). Conclusion: All individuals presented a severe to profound bilateral hearing loss, related to ANSD.